Legal socialization and selective exposure to "cop-watching" websites. Issue 6 (21st November 2019) - Moule Jr, Richard K.; Parry, Megan M.; Fox, Bryanna
Abstract : Purpose: The legitimacy crisis faced by law enforcement has been suggested to be the result of a new media environment where citizens can record encounters with police and place these recordings online. The purpose of this paper is to examine the motives of individuals who cop-watch, or record the police, but not the factors influencing visiting cop-watching websites. Design/methodology/approach: Using a cross-sectional, national sample of 702 American adults, and drawing on theories of legal socialization and selective exposure, the current study examines the prevalence and correlates visiting "cop-watching" websites. Findings: Approximately 9 percent of the sample reports having ever visited these sites. Results from a series of logistic regressions indicate legal cynicism is positively associated with having ever visited these sites, having done so recently, following these sites on social media and visiting these sites more frequently after Ferguson. Police legitimacy reduced the likelihood that individuals had ever visited these sites, but was unrelated to other outcomes. Research limitations/implications: The cross-sectional nature of the survey precludes discussion of causality, but results are fairly consistent with theoretical expectations. Originality/value: The current study reflects an early attempt to understand correlates of public consumption of "cop-watching" material.